EXAMINING THE PERSONAL FACTORS AFFECTING LICENSURE EXAMINATION PREPARATION - Melvi A Briones,LPT; Virginia A. Romero (Journal of English Education and Linguistics, 2020)
Students’ high performance, if not 100% passing rate, in taking the Licensure Examination for Teachers (LET) is the ultimate goal of every Teacher Education Institutions (TEI). Hence, it requires all the necessary preparations not only what the school can provide but also with the examinees’ personal accountability. This paper investigated the present condition of the respondents specifically on their personal preparedness along self-motivation, study skills and habits, and time management. There were 40 (22 BEED and 18 BSED practicum students) of the University of Nueva Caceres College of Education, who were used as the respondents of this study. These students were also preparing for their LET Examination through once a week assessment classes for the entire duration of their practicum. Survey revealed that respondents were exceptionally high in their personal drive along self-motivation but their commitment/goal setting needs to be defined. The use of resources was noted to be very highly used along study skills but health habits was the least given attention. It was further revealed that time management skills of the respondents were very high along deciding and starting their study routine but are struggling with difficult task which are not of their interest but might be highly relevant to their professional examination.